A high nickel ternary positive electrode material with low residual alkali, high specific capacity and high cycle stability and a preparation method thereof

Through the co-covering of aluminum metaphosphate and lithium phosphate and the composite coating of graphene, carbon nanotubes, and conductive carbon black, the residual alkali problem on the surface of high-nickel ternary positive electrode materials is solved, and its specific capacity and cycle stability are improved , achieving higher electrochemical properties.

CN118738357BActive Publication Date: 2025-01-07LANZHOU RESOURCES & ENVIRONMENT VOC TECH COLLEGE
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411210581.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2025-01-07
Estimated Expiration
2044-08-30

AI Technical Summary

Technical Problem

High-nickel ternary cathode material reacts with water and carbon dioxide in the air to produce residual alkali, resulting in an increase in the surface alkali content, affecting its structural stability and electrochemical properties. Especially when the molar content of nickel elements exceeds 80%, there is poor interface stability. and irreversible phase change problem hinders its storage and processing performance.

Method used

Using aluminum metaphosphate as the coating agent, the residual alkali on the surface of high-nickel ternary cathode material is converted into a co-coated layer of aluminum phosphate and lithium phosphate through the sintering process, and is then combined with graphene, carbon nanotubes and conductive carbon black. To improve the conductivity and cycle stability of the material.

Benefits of technology

It significantly reduces the residual alkali content of high-nickel ternary cathode material, improves its specific capacity and cycle stability, increases the specific capacity for the first discharge by 5~10mAh/g, and increases the capacity retention rate of 500 cycles by more than 5%, and the process is simple Easy to industrialize.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118738357B_ABST
    Figure CN118738357B_ABST
Patent Text Reader

Abstract

The invention discloses a high-nickel ternary positive electrode material with low residual alkali, high specific capacity and high cycle stability and a preparation method thereof. The preparation method comprises the following steps: preparing a primary coating agent dispersion, mixing the high-nickel ternary positive electrode material with the primary coating agent dispersion, vacuum drying the primary mixed material, solid-phase sintering the primary coated high-nickel ternary positive electrode material, preparing a secondary coating agent dispersion, mixing the primary coated high-nickel ternary positive electrode material matrix with the secondary coating agent dispersion, and vacuum drying the secondary mixed material; the prepared high-nickel ternary positive electrode material comprises a LiNi x Co y Mn z O2 (0.8≤x<1,0
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of preparation of positive electrode materials for lithium ion batteries, and in particular to a high-nickel ternary positive electrode material with low residual alkali, high specific capacity and high cycle stability and a preparation method thereof. Background Art

[0002] As the requirements for high energy density and low cost of lithium-ion power batteries for new energy vehicles continue to increase, nickel-cobalt-manganese ternary positive electrode materials continue to develop towards high nickel content, low cobalt content, and low manganese content. However, with the increase in nickel content and the decrease in cobalt and manganese content, high-nickel ternary positive electrode materials will react with water and carbon dioxide when exposed to air, and it is easy to generate a layer of residual alkali (LiOH and Li2CO3) on the surface of the material. As the residual alkali content on the surface of the material increases, the structural stability, interface stability and safety of the material will gradually deteriorate. Especially for positive electrode materials with a nickel molar content of more than 80%, the increase in the residual alkali content on the surface will seriously hinder the stable performance and commercial application of their storage performance, processing performance, and electrochemical performance. Therefore, how to effectively regulate the residual alkali content of high-nickel ternary positive electrode materials to improve their interface stability and thus improve their electrochemical performance is the focus and hot spot of current industry research.

[0003] In recent years, researchers have done a lot of work, including element doping and surface coating, to improve the structural stability and interface stability of high-nickel ternary positive electrode materials, thereby improving their electrochemical performance. Although there are certain effects, they cannot solve the problems of poor interface stability and irreversible phase change of high-nickel ternary positive electrode materials. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a high-nickel ternary positive electrode material with low residual alkali, high specific capacity and high cycle stability. Aluminum metaphosphate is used as a coating agent, and the residual alkali on the surface of the high-nickel ternary positive electrode material is converted into an aluminum phosphate and lithium phosphate co-coating layer during the sintering process, so as to effectively reduce the amount of residual alkali on the surface of the high-nickel ternary positive electrode material and inhibit irreversible phase change. After composite coating with graphene, carbon nanotubes and conductive carbon black, the conductive properties of the high-nickel ternary positive electrode material can be improved, thereby significantly improving its specific capacity and cycle stability.

[0005] Another object of the present invention is to provide a high-nickel ternary positive electrode material with low residual alkali, high specific capacity and high cycle stability prepared by the above method.

[0006] To achieve its purpose, the present invention adopts the following technical solutions:

[0007] The present invention provides a method for preparing a high-nickel ternary positive electrode material with low residual alkali, high specific capacity and high cycle stability, comprising the following steps:

[0008] Step 1. Preparation of the primary coating agent aluminum metaphosphate dispersion:

[0009] Mix aluminum metaphosphate and N-methylpyrrolidone at a mass ratio of 0.01~0.03:1, and then add them to a high-speed pre-disperser for pre-dispersion to form a premixed dispersion; then transfer the premixed dispersion to a grinder, start the grinder, and grind for 2~6h while maintaining the temperature of the dispersion at 5~15°C to obtain a ground dispersion; subject the ground dispersion to sanding and homogenization treatments, and remove magnetic foreign objects with a magnetic foreign object removal device to form a uniformly dispersed and stable primary coating agent aluminum metaphosphate dispersion;

[0010] Step 2. Mixing of the high-nickel ternary cathode material and the primary coating agent aluminum metaphosphate dispersion:

[0011] Stir and mix the high-nickel ternary cathode material and the primary coating agent aluminum metaphosphate dispersion in Step 1 at a mass ratio of 0.5~1.5:1 to obtain a primary mixed material; the molecular formula of the high-nickel ternary cathode material is LiNi x Co y Mn z O2, where 0.80 ≤ x < 1, 0 < y < 0.2, 0 < z < 0.2, and x + y + z = 1; preferably, 0.80 ≤ x ≤ 0.88, 0.09 ≤ y ≤ 0.12, 0.03 ≤ z ≤ 0.1, and x + y + z = 1;

[0012] Step 3. Vacuum drying of the mixed material:

[0013] Vacuum dry and screen the primary mixed material in Step 2 to obtain a primary coated high-nickel ternary cathode material matrix;

[0014] Step 4. Solid-phase sintering of the primary coated high-nickel ternary cathode material matrix:

[0015] Place the primary coated high-nickel ternary cathode material matrix in Step 3 in a box-type atmosphere resistance furnace, and sinter it under an inert gas atmosphere with a flow rate of 30~60L / h. Heat it at a rate of 1~5°C / min to 500~700°C and hold for 4~8h, then cool it at a rate of -0.3~-0.5°C / min to 300°C, and then naturally cool it to room temperature with the furnace. Screen the produced sintered material through a 200~400-mesh nylon sieve to obtain a high-nickel ternary cathode material powder co-coated with aluminum phosphate and lithium phosphate; perform electron microscopy characterization on the high-nickel ternary cathode material powder, and observe the lattices of aluminum phosphate and lithium phosphate on its surface. That is to say, a co-coated layer of aluminum phosphate and lithium phosphate is obtained after solid-phase sintering;

[0016] Step 5. Preparation of the secondary coating agent dispersion:

[0017] The composite coating agent, polyvinyl pyrrolidone and nitrogen methyl pyrrolidone are sequentially put into a high-speed pre-disperser for pre-dispersion to form a premixed dispersion; then the premixed dispersion is added to a grinder, the grinder is turned on, and the dispersion is kept at a temperature of 5-15°C for grinding for 4-8 hours to obtain a grinding dispersion; the grinding dispersion is subjected to sand milling and homogenization to form a secondary coating agent dispersion with stable and uniform dispersion; the composite coating agent is composed of graphene, carbon nanotubes and conductive carbon black; in terms of mass percentage, the premixed dispersion contains 0.5-3% graphene, 0.5-3% carbon nanotubes, 0.5-1% conductive carbon black, 93-97% nitrogen methyl pyrrolidone, and 0.1-1% polyvinyl pyrrolidone;

[0018] Step 6: Mixing the high nickel ternary cathode material powder co-coated with aluminum phosphate and lithium phosphate with the secondary coating agent dispersion:

[0019] The high nickel ternary positive electrode material powder co-coated with aluminum phosphate and lithium phosphate in step 4 is uniformly mixed with the secondary coating agent dispersion in step 5 at a mass ratio of 0.5 to 1.5:1 to obtain a secondary mixed material;

[0020] Step 7: Drying and screening of mixed materials:

[0021] The secondary mixed material in step six is ​​dried and sieved to obtain a high-nickel ternary positive electrode material coated with a composite coating agent.

[0022] As a further preferred embodiment of the technical solution of the present invention, in step 1, a high-speed pre-dispersion tank is used for pre-dispersion, and the high-speed pre-dispersion stirring speed is 300-500 r / min, and the stirring time is 30-60 min.

[0023] Furthermore, in step 1, the grinding machine has a rotation speed of 2000-3000 r / min, a sand milling homogenization time of 2-6 h, and a dispersion temperature of 5-15° C.

[0024] Furthermore, in step three, drying is performed in a blast drying oven at a drying temperature of 100-120° C. and a drying time of 10-20 h; and screening is performed using a 200-400 mesh nylon sieve.

[0025] Furthermore, in step 4, the inert atmosphere is an argon atmosphere.

[0026] Furthermore, in step six, the mixing equipment is a vacuum mixer, and the mixing time is 8 to 20 hours.

[0027] Furthermore, in step seven, drying is performed in a vacuum drying oven with a vacuum degree of -0.2 to -0.7 MPa and drying at 80 to 110° C. for 10 to 20 hours; and screening is performed using a 200 to 400 mesh nylon sieve.

[0028] Furthermore, the primary coating agent aluminum metaphosphate dispersion in step one and the secondary coating agent dispersion in step five are treated to remove magnetic foreign matter; the treatment to remove magnetic foreign matter is to use an 8000~10000Gs magnetic foreign matter removal device (refer to patent CN105470579A) to remove magnetic foreign matter 4~8 times.

[0029] Furthermore, the primary coating agent aluminum metaphosphate dispersion in step one and the secondary coating agent dispersion in step five have a main controlled impurity Fe element content of <50ppm, and a single element content of Cr, Ni, Zn or Cu is <10ppm.

[0030] The above method can be used to prepare a high-nickel ternary positive electrode material with a residual alkali content of less than 3000 ppm, high specific capacity and high cycle stability.

[0031] The beneficial effects of the present invention are:

[0032] 1. The preparation method of the present invention first uses aluminum metaphosphate to coat the high-nickel ternary positive electrode material once and obtains an aluminum phosphate and lithium phosphate co-coating layer through solid phase sintering; then uses graphene, carbon nanotubes, and conductive carbon black composite coating agents to coat the high-nickel ternary positive electrode material that has been coated once for a second time. This method can effectively reduce the residual alkali content in the high-nickel ternary positive electrode material and prevent the occurrence of side reactions at the material interface, and can also improve the conductivity of the high-nickel ternary positive electrode material and significantly improve its cycle stability.

[0033] 2. The button cell prepared by the high-nickel ternary positive electrode material with low residual alkali, high specific capacity and high cycle stability described in the present invention can increase its first discharge specific capacity (2.8~4.3V) by 5~10mAh / g compared with the uncoated high-nickel ternary positive electrode material under the same conditions, and the capacity retention rate after 500 cycles in the full battery can be increased by more than 5% compared with the uncoated high-nickel ternary positive electrode material under the same conditions, and has obvious advantages in both discharge specific capacity and cycle performance.

[0034] 3. The preparation method of the present invention has simple process, convenient operation, easy to realize industrial production, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is a SEM image of a high-nickel ternary positive electrode material of Example 2 of the present invention, which is co-coated with aluminum phosphate and lithium phosphate once, and is composite-coated with graphene, carbon nanotubes, and conductive carbon black twice;

[0036] Figure 2 This is a SEM image of the uncoated high-nickel ternary positive electrode material of Comparative Example 1;

[0037] Figure 3A schematic diagram of the first discharge specific capacity of the high nickel ternary positive electrode material of Example 2 in which aluminum phosphate and lithium phosphate are co-coated once and graphene, carbon nanotubes and conductive carbon black are compositely coated twice;

[0038] Figure 4 A schematic diagram of the first discharge specific capacity of the high nickel ternary positive electrode material of Example 5 in which aluminum phosphate and lithium phosphate are co-coated once and graphene, carbon nanotubes and conductive carbon black are compositely coated twice;

[0039] Figure 5 A schematic diagram of the first discharge specific capacity of the high nickel ternary positive electrode material of Example 6 in which aluminum phosphate and lithium phosphate are co-coated once and graphene, carbon nanotubes and conductive carbon black are compositely coated twice;

[0040] Figure 6 This is a schematic diagram of the first discharge specific capacity of the uncoated high-nickel ternary positive electrode material of Comparative Example 1;

[0041] Figure 7 This is a schematic diagram of the first discharge specific capacity of the uncoated high-nickel ternary positive electrode material of Comparative Example 2;

[0042] Figure 8 This is a schematic diagram of the first discharge specific capacity of the uncoated high-nickel ternary positive electrode material of comparative example 3. DETAILED DESCRIPTION

[0043] In order to better understand the present invention, the content of the present invention is further explained below in combination with the accompanying drawings and embodiments, but the protection content of the present invention is not limited to the following embodiments.

[0044] Example 1

[0045] Preparation of a LiNi with low residual alkali, high specific capacity and high cycle stability 0.83 Co 0.12 Mn 0.05 O2 high nickel ternary positive electrode material, the specific steps are:

[0046] (1) Weigh 10 g of aluminum metaphosphate and 990 g of nitrogen methyl pyrrolidone, add them to a high-speed pre-disperser for pre-dispersion, stir at a speed of 350 r / min, and stir for 35 min; then transfer the premixed dispersion to a grinder, turn on the grinder, grind at a speed of 2200 r / min for 3.5 h, keep the dispersion temperature at 10°C, and obtain a ground dispersion. Sand mill the ground dispersion at 10°C for 3 h, and remove magnetic foreign matter 6 times with a 10000 Gs magnetic foreign matter removal device to obtain a primary aluminum metaphosphate coating agent dispersion with a mass fraction of 1%.

[0047] (2) Weigh 800g LiNi 0.83 Co 0.12Mn 0.05 The O2 high-nickel ternary positive electrode material is added to a magnetic stirrer, and then 800 g of the primary aluminum metaphosphate coating agent dispersion obtained in step (1) is added, and the mixture is stirred for 3 hours to obtain a uniform primary mixed material.

[0048] (3) The primary mixed material obtained in step (2) is transferred to a forced air drying oven, dried at 105° C. for 12 h, and then sieved using a 250-mesh nylon sieve to obtain a primary coated high-nickel ternary positive electrode material matrix.

[0049] (4) The primary coated high-nickel ternary positive electrode material matrix obtained in step (3) is placed in a corundum sagger, placed in a box-type atmosphere resistance furnace, and sintered in an argon atmosphere with a flow rate of 45 L / h: the temperature is raised to 600°C at 3°C / min, kept at this temperature for 6 hours, then cooled to 300°C at a rate of -0.4°C / min, and then naturally cooled to room temperature with the furnace. The sintered material is sieved with a 300-mesh nylon sieve to obtain LiNi co-coated with aluminum phosphate and lithium phosphate. 0.83 Co 0.12 Mn 0.05 O2 high nickel ternary positive electrode material powder, residual alkali content is 2540ppm.

[0050] (5) Weigh 30 g of graphene, 10 g of carbon nanotubes, and 10 g of conductive carbon black (mass ratio 3:1:1), and weigh 10 g of polyvinyl pyrrolidone as a dispersant and 940 g of nitrogen methyl pyrrolidone as a solvent, and put them into a high-speed pre-disperser in sequence for pre-dispersion at a stirring speed of 300 r / min and a stirring time of 50 min; then start the grinder and grind at a grinder speed of 2500 r / min and a temperature of 10°C for 6 h to obtain a grinding dispersion; sand grind the grinding dispersion for 6 h, and use a 10000Gs magnetic foreign matter removal device to remove magnetic foreign matter 6 times to prepare a secondary coating agent dispersion with a carbon mass fraction of 5%.

[0051] (6) Weigh 500 g of LiNi obtained in step (4) 0.83 Co 0.12 Mn 0.05 The O2 high-nickel ternary positive electrode material powder is added into a vacuum mixer, and then 500 g of the secondary coating agent dispersion obtained in step (5) is added, and the mixture is stirred for 12 hours to obtain a uniform secondary mixed material, the impurity Fe content of which is 20 ppm, and the content of the single element Cr, Ni, Zn or Cu is all <5 ppm.

[0052] (7) The secondary mixed material obtained in step (6) is transferred to a vacuum drying oven, dried at 100° C. and a vacuum degree of −0.7 MPa for 12 h, and then sieved using a 300-mesh nylon sieve to obtain a high-nickel ternary positive electrode material coated with a composite coating agent.

[0053] The twice-coated LiNi prepared in step (7) 0.83 Co 0.12 Mn 0.05 The button-type CR2025 half-cell made of O2 high-nickel ternary positive electrode material has an initial discharge capacity of 216.7mAh / g and a coulombic efficiency of 90.2% at a cut-off voltage of 2.8-4.3V and a rate of 0.1C. The cylindrical 18650 full-cell was tested for electrochemical performance. The charge and discharge cycles were repeated 500 times at a cut-off voltage of 2.8-4.2V and a rate of 0.5C / 0.5C, and the discharge capacity retention rate could reach over 86.2%.

[0054] Example 2

[0055] Preparation of a LiNi with low residual alkali, high specific capacity and high cycle stability 0.83 Co 0.12 Mn 0.05 O2 high nickel ternary positive electrode material, the specific steps are:

[0056] (1) Weigh 20 g of aluminum metaphosphate and 980 g of nitrogen methyl pyrrolidone, add them to a high-speed pre-disperser for pre-dispersion, stir at a speed of 400 r / min, and stir for 45 min; then transfer the premixed dispersion to a grinder, turn on the grinder, and grind at a speed of 2500 r / min for 2.5 h to obtain a grinding dispersion, sand-mill the grinding dispersion at 10° C. for 4 h, and use a 10000 Gs magnetic foreign matter removal device to remove magnetic foreign matter 4 times to obtain a primary aluminum metaphosphate coating agent dispersion with a mass fraction of 2%.

[0057] (2) Weigh 800g LiNi 0.83 Co 0.12 Mn 0.05 The O2 high-nickel ternary positive electrode material is added to a magnetic stirrer, and then 800 g of the primary aluminum metaphosphate coating agent dispersion obtained in step (1) is added, and the mixture is stirred for 6 hours to obtain a uniform primary mixed material.

[0058] (3) The primary mixed material obtained in step (2) is transferred to a forced air drying oven, dried at 100° C. for 16 h, and then sieved using a 300-mesh nylon sieve to obtain a primary coated high-nickel ternary positive electrode material matrix.

[0059] (4) The primary coated high-nickel ternary positive electrode material matrix obtained in step (3) is placed in a corundum sagger, placed in a box-type atmosphere resistance furnace, and sintered in an argon atmosphere with a flow rate of 48 L / h: the temperature is raised to 620°C at 4°C / min, kept at this temperature for 5 h, then cooled to 300°C at a rate of -0.4°C / min, and then naturally cooled to room temperature with the furnace. The sintered material is sieved with a 300-mesh nylon sieve to obtain LiNi co-coated with aluminum phosphate and lithium phosphate. 0.83 Co 0.12 Mn 0.05 O2 high nickel ternary positive electrode material powder, residual alkali content is 2410ppm.

[0060] (5) Weigh 20 g of graphene, 10 g of carbon nanotubes, and 10 g of conductive carbon black (mass ratio 2:1:1), and weigh 10 g of polyvinyl pyrrolidone as a dispersant and 950 g of nitrogen methyl pyrrolidone as a solvent, and put them into a high-speed pre-disperser in sequence for pre-dispersion at a stirring speed of 300 r / min and a stirring time of 50 min; then start the grinder and grind for 5 h at a grinder speed of 2800 r / min and a temperature of 10°C to obtain a grinding dispersion; sand grind the grinding dispersion for 6 h, and use a 10000Gs magnetic foreign matter removal device to remove magnetic foreign matter 6 times to prepare a secondary coating agent dispersion with a carbon mass fraction of 5%.

[0061] (6) Weigh 500 g of LiNi obtained in step (4) 0.83 Co 0.12 Mn 0.05 The O2 high-nickel ternary positive electrode material powder is added into a vacuum mixer, and then 500 g of the secondary coating agent dispersion obtained in step (5) is added, and the mixture is stirred for 12 hours to obtain a uniform secondary mixed material, the impurity Fe content of which is 21 ppm, and the content of the single element Cr, Ni, Zn or Cu is <5 ppm.

[0062] (7) The secondary mixed material obtained in step (6) was transferred to a vacuum drying oven, dried at 100° C. and a vacuum degree of -0.7 MPa for 12 h, and then sieved using a 300-mesh nylon sieve to obtain a high-nickel ternary positive electrode material coated with a composite coating agent ( Figure 1 ).

[0063] The twice-coated LiNi prepared in step (7) 0.83 Co 0.12 Mn 0.05 The button-type CR2025 half-cell made of O2 high-nickel ternary positive electrode material has a first discharge capacity of 217.2mAh / g ( Figure 3), the coulombic efficiency reached 91.1%; it was made into a cylindrical 18650 full battery for electrochemical performance testing. After 500 charge and discharge cycles at a cut-off voltage of 2.8-4.2V and a rate of 0.5C / 0.5C, the discharge specific capacity retention rate could reach more than 87.7%.

[0064] Example 3

[0065] Preparation of a LiNi with low residual alkali, high specific capacity and high cycle stability 0.83 Co 0.12 Mn 0.05 O2 high nickel ternary positive electrode material, the specific steps are:

[0066] (1) Weigh 30 g of aluminum metaphosphate and 970 g of nitrogen methyl pyrrolidone, add them to a high-speed pre-disperser for pre-dispersion, stir at a speed of 400 r / min, and stir for 45 min; then transfer the premixed dispersion to a grinder, turn on the grinder, and grind at a speed of 2800 r / min for 2 h to obtain a grinding dispersion, sand-mill the grinding dispersion at 10° C. for 6 h, and use a 10000 Gs magnetic foreign matter removal device to remove magnetic foreign matter 4 times to obtain a primary aluminum metaphosphate coating agent dispersion with a mass fraction of 3%.

[0067] (2) Weigh 800g LiNi 0.83 Co 0.12 Mn 0.05 The O2 high-nickel ternary positive electrode material is added to a magnetic stirrer, and then 800 g of the primary aluminum metaphosphate coating agent dispersion obtained in step (1) is added, and the mixture is stirred for 6 hours to obtain a uniform primary mixed material.

[0068] (3) The primary mixed material obtained in step (2) is transferred to a forced air drying oven, dried at 100° C. for 16 h, and then sieved using a 250-mesh nylon sieve to obtain a primary coated high-nickel ternary positive electrode material matrix.

[0069] (4) The primary coated high-nickel ternary positive electrode material matrix obtained in step (3) is placed in a corundum sagger, placed in a box-type atmosphere resistance furnace, and sintered in an argon atmosphere with a flow rate of 42 L / h: the temperature is raised to 580°C at 2°C / min, kept at this temperature for 8 hours, and then cooled to 300°C at a rate of -0.4°C / min, and then naturally cooled to room temperature with the furnace. The sintered material is sieved with a 300-mesh nylon sieve to obtain LiNi co-coated with aluminum phosphate and lithium phosphate. 0.83 Co 0.12 Mn 0.05 O2 high nickel ternary positive electrode material powder, residual alkali content is 2370ppm.

[0070] (5) Weigh 30 g of graphene, 10 g of carbon nanotubes, and 10 g of conductive carbon black (mass ratio 3:1:1), and weigh 10 g of polyvinyl pyrrolidone as a dispersant and 940 g of nitrogen methyl pyrrolidone as a solvent, and put them into a high-speed pre-disperser in sequence for pre-dispersion at a stirring speed of 300 r / min and a stirring time of 50 min; then start the grinder and grind at a grinder speed of 2600 r / min and a temperature of 10°C for 6 h to obtain a grinding dispersion; sand grind the grinding dispersion for 6 h, and use a 10000Gs magnetic foreign matter removal device to remove magnetic foreign matter 6 times to prepare a secondary coating agent dispersion with a carbon mass fraction of 5%.

[0071] (6) Weigh 500 g of LiNi obtained in step (4) 0.83 Co 0.12 Mn 0.05 The O2 high-nickel ternary positive electrode material powder is added into a vacuum mixer, and then 500 g of the secondary coating agent dispersion obtained in step (5) is added, and the mixture is stirred for 12 hours to obtain a uniform secondary mixed material, the impurity Fe content of which is 33 ppm, and the content of the single element Cr, Ni, Zn or Cu is <5 ppm.

[0072] (7) The secondary mixed material obtained in step (6) is transferred to a vacuum drying oven, dried at 100° C. and a vacuum degree of −0.7 MPa for 12 h, and then sieved using a 300-mesh nylon sieve to obtain a high-nickel ternary positive electrode material coated with a composite coating agent.

[0073] The twice-coated LiNi prepared in step (7) 0.83 Co 0.12 Mn 0.05 The button-type CR2025 half-cell made of O2 high-nickel ternary positive electrode material has an initial discharge capacity of 215.2mAh / g and a coulombic efficiency of 90.3% at a cut-off voltage of 2.8-4.3V and a rate of 0.1C. The cylindrical 18650 full-cell was tested for electrochemical performance. The charge and discharge cycles were repeated 500 times at a cut-off voltage of 2.8-4.2V and a rate of 0.5C / 0.5C, and the discharge capacity retention rate could reach over 86.0%.

[0074] Example 4

[0075] Preparation of a LiNi with low residual alkali, high specific capacity and high cycle stability 0.83 Co 0.11 Mn 0.06 O2 high nickel ternary positive electrode material, the specific steps are:

[0076] (1) Weigh 20 g of aluminum metaphosphate and 980 g of nitrogen methyl pyrrolidone, add them to a high-speed pre-disperser for pre-dispersion, stir at a speed of 350 r / min, and stir for 35 min; then transfer the premixed dispersion to a grinder, turn on the grinder, and grind at a speed of 2200 r / min for 3.5 h to obtain a grinding dispersion, sand-mill the grinding dispersion at 10° C. for 3 h, and use a 10000 Gs magnetic foreign matter removal device to remove magnetic foreign matter 6 times to obtain a primary aluminum metaphosphate coating agent dispersion with a mass fraction of 2%.

[0077] (2) Weigh 800g LiNi 0.83 Co 0.11 Mn 0.06 The O2 high-nickel ternary positive electrode material is added to a magnetic stirrer, and then 800 g of the primary aluminum metaphosphate coating agent dispersion obtained in step (1) is added, and the mixture is stirred for 3 hours to obtain a uniform primary mixed material.

[0078] (3) The primary mixed material obtained in step (2) is transferred to a forced air drying oven, dried at 105° C. for 12 h, and then sieved using a 250-mesh nylon sieve to obtain a primary coated high-nickel ternary positive electrode material matrix.

[0079] (4) The primary coated high-nickel ternary positive electrode material matrix obtained in step (3) is placed in a corundum sagger, placed in a box-type atmosphere resistance furnace, and sintered in an argon atmosphere with a flow rate of 45 L / h: the temperature is raised to 600°C at 3°C / min, kept at this temperature for 6 hours, then cooled to 300°C at a rate of -0.4°C / min, and then naturally cooled to room temperature with the furnace. The sintered material is sieved with a 300-mesh nylon sieve to obtain LiNi co-coated with aluminum phosphate and lithium phosphate. 0.83 Co 0.11 Mn 0.06 O2 high nickel ternary positive electrode material powder, residual alkali content is 2460ppm.

[0080] (5) Weigh 20 g of graphene, 10 g of carbon nanotubes, and 10 g of conductive carbon black (mass ratio 2:1:1), and weigh 10 g of polyvinyl pyrrolidone as a dispersant and 950 g of nitrogen methyl pyrrolidone as a solvent, and put them into a high-speed pre-disperser in sequence for pre-dispersion at a stirring speed of 300 r / min and a stirring time of 50 min; then start the grinder and grind at a grinder speed of 2500 r / min and a temperature of 10°C for 6 h to obtain a grinding dispersion; sand grind the grinding dispersion for 6 h, and use a 10000Gs magnetic foreign matter removal device to remove magnetic foreign matter 6 times to prepare a secondary coating agent dispersion with a carbon mass fraction of 5%.

[0081] (6) Weigh 500 g of LiNi obtained in step (4) 0.83 Co 0.11Mn 0.06 The O2 high-nickel ternary positive electrode material powder is added into a vacuum mixer, and then 500 g of the secondary coating agent dispersion obtained in step (5) is added, and the mixture is stirred for 12 hours to obtain a uniform secondary mixed material, the impurity Fe content of which is 29 ppm, and the content of the single element Cr, Ni, Zn or Cu is <5 ppm.

[0082] (7) The secondary mixed material obtained in step (6) is transferred to a vacuum drying oven, dried at 100° C. and a vacuum degree of −0.7 MPa for 12 h, and then sieved using a 300-mesh nylon sieve to obtain a high-nickel ternary positive electrode material coated with a composite coating agent.

[0083] The twice-coated LiNi prepared in step (7) 0.83 Co 0.11 Mn 0.06 The button-type CR2025 half-cell made of O2 high-nickel ternary positive electrode material has an initial discharge capacity of 215.3mAh / g and a coulombic efficiency of 90.1% at a cut-off voltage of 2.8-4.3V and a rate of 0.1C. The cylindrical 18650 full-cell was tested for electrochemical performance. The charge and discharge cycles were repeated 500 times at a cut-off voltage of 2.8-4.2V and a rate of 0.5C / 0.5C, and the discharge capacity retention rate could reach over 86.1%.

[0084] Example 5

[0085] Preparation of a LiNi with low residual alkali, high specific capacity and high cycle stability 0.80 Co 0.10 Mn 0.10 O2 high nickel ternary positive electrode material, the specific steps are:

[0086] (1) Weigh 20 g of aluminum metaphosphate and 980 g of nitrogen methyl pyrrolidone, add them to a high-speed pre-disperser for pre-dispersion, stir at a speed of 400 r / min, and stir for 45 min; then transfer the premixed dispersion to a grinder, turn on the grinder, and grind at a speed of 2500 r / min for 2.5 h to obtain a grinding dispersion, sand-mill the grinding dispersion at 10° C. for 4 h, and use a 10000 Gs magnetic foreign matter removal device to remove magnetic foreign matter 4 times to obtain a primary aluminum metaphosphate coating agent dispersion with a mass fraction of 2%.

[0087] (2) Weigh 800g LiNi 0.80 Co 0.10 Mn 0.10 The O2 high-nickel ternary positive electrode material is added to a magnetic stirrer, and then 800 g of the primary aluminum metaphosphate coating agent dispersion obtained in step (1) is added, and the mixture is stirred for 6 hours to obtain a uniform primary mixed material.

[0088] (3) The primary mixed material obtained in step (2) is transferred to a forced air drying oven, dried at 100° C. for 16 h, and then sieved using a 300-mesh nylon sieve to obtain a primary coated high-nickel ternary positive electrode material matrix.

[0089] (4) The primary coated high-nickel ternary positive electrode material matrix obtained in step (3) is placed in a corundum sagger, placed in a box-type atmosphere resistance furnace, and sintered in an argon atmosphere with a flow rate of 48 L / h: the temperature is raised to 620°C at 3°C / min, kept at this temperature for 5 h, then cooled to 300°C at a rate of -0.3°C / min, and then naturally cooled to room temperature with the furnace. The sintered material is sieved with a 300-mesh nylon sieve to obtain LiNi co-coated with aluminum phosphate and lithium phosphate. 0.80 Co 0.10 Mn 0.10 O2 high nickel ternary positive electrode material powder, residual alkali content is 2230ppm.

[0090] (5) Weigh 20 g of graphene, 10 g of carbon nanotubes, and 10 g of conductive carbon black (mass ratio 2:1:1), and weigh 10 g of polyvinyl pyrrolidone as a dispersant and 950 g of nitrogen methyl pyrrolidone as a solvent, and put them into a high-speed pre-disperser in sequence for pre-dispersion at a stirring speed of 300 r / min and a stirring time of 50 min; then start the grinder and grind for 5 h at a grinder speed of 2800 r / min and a temperature of 10°C to obtain a grinding dispersion; sand grind the grinding dispersion for 6 h, and use a 10000Gs magnetic foreign matter removal device to remove magnetic foreign matter 6 times to prepare a secondary coating agent dispersion with a carbon mass fraction of 5%.

[0091] (6) Weigh 500 g of LiNi obtained in step (4) 0.80 Co 0.10 Mn 0.10 The O2 high-nickel ternary positive electrode material powder is added into a vacuum mixer, and then 500 g of the secondary coating agent dispersion obtained in step (5) is added, and the mixture is stirred for 12 hours to obtain a uniform secondary mixed material, the impurity Fe content of which is 18 ppm, and the content of the single element Cr, Ni, Cu or Zn is <5 ppm.

[0092] (7) The secondary mixed material obtained in step (6) is transferred to a vacuum drying oven, dried at 100° C. and a vacuum degree of −0.7 MPa for 12 h, and then sieved using a 300-mesh nylon sieve to obtain a high-nickel ternary positive electrode material coated with a composite coating agent.

[0093] The twice-coated LiNi prepared in step (7) 0.80 Co 0.10 Mn 0.10The button-type CR2025 half-cell made of O2 high-nickel ternary positive electrode material has a first discharge capacity of 210.6mAh / g ( Figure 4 ), the coulombic efficiency reached 91.4%; it was made into a cylindrical 18650 full battery for electrochemical performance testing. After 500 charge and discharge cycles at a cut-off voltage of 2.8-4.2V and a rate of 0.5C / 0.5C, the discharge specific capacity retention rate could reach more than 88.1%.

[0094] Example 6

[0095] Preparation of a LiNi with low residual alkali, high specific capacity and high cycle stability 0.88 Co 0.09 Mn 0.03 O2 high nickel ternary positive electrode material, the specific steps are:

[0096] (1) Weigh 20 g of aluminum metaphosphate and 980 g of nitrogen methyl pyrrolidone, add them into a high-speed pre-disperser for pre-dispersion, stir at a speed of 400 r / min, and stir for 45 min; then transfer the premixed dispersion to a grinder, turn on the grinder, and grind at a speed of 2200 r / min for 5 h to obtain a grinding dispersion, sand-mill the grinding dispersion at 10° C. for 6 h, and remove magnetic foreign matter 4 times with a 10000 Gs magnetic foreign matter removal device to obtain a primary aluminum metaphosphate coating agent dispersion with a mass fraction of 2%.

[0097] (2) Weigh 800g LiNi 0.88 Co 0.09 Mn 0.03 The O2 high-nickel ternary positive electrode material is added to a magnetic stirrer, and then 800 g of the primary aluminum metaphosphate coating agent dispersion obtained in step (1) is added, and the mixture is stirred for 6 hours to obtain a uniform primary mixed material.

[0098] (3) The primary mixed material obtained in step (2) is transferred to a forced air drying oven, dried at 100° C. for 16 h, and then sieved using a 250-mesh nylon sieve to obtain a primary coated high-nickel ternary positive electrode material matrix.

[0099] (4) The primary coated high-nickel ternary positive electrode material matrix obtained in step (3) is placed in a corundum sagger, placed in a box-type atmosphere resistance furnace, and sintered in an argon atmosphere with a flow rate of 48 L / h: the temperature is raised to 580°C at 4°C / min, kept at this temperature for 8 hours, then cooled to 300°C at a rate of -0.5°C / min, and then naturally cooled to room temperature with the furnace. The sintered material is sieved with a 300-mesh nylon sieve to obtain LiNi co-coated with aluminum phosphate and lithium phosphate. 0.88 Co 0.09 Mn 0.03O2 high nickel ternary positive electrode material powder, residual alkali content is 2780ppm.

[0100] (5) Weigh 20 g of graphene, 10 g of carbon nanotubes, and 10 g of conductive carbon black (mass ratio 2:1:1), and weigh 10 g of polyvinyl pyrrolidone as a dispersant and 950 g of nitrogen methyl pyrrolidone as a solvent, and put them into a high-speed pre-disperser in sequence for pre-dispersion at a stirring speed of 300 r / min and a stirring time of 50 min; then start the grinder and grind at a grinder speed of 2600 r / min and a temperature of 10°C for 6 h to obtain a grinding dispersion; sand grind the grinding dispersion for 6 h, and use a 10000Gs magnetic foreign matter removal device to remove magnetic foreign matter 6 times to prepare a secondary coating agent dispersion with a carbon mass fraction of 5%.

[0101] (6) Weigh 500 g of LiNi obtained in step (4) 0.88 Co 0.09 Mn 0.03 The O2 high-nickel ternary positive electrode material powder is added into a vacuum mixer, and then 500 g of the secondary coating agent dispersion obtained in step (5) is added, and the mixture is stirred for 12 hours to obtain a uniform secondary mixed material, the impurity Fe content of which is 26 ppm, and the content of the single element Cr, Ni, Zn or Cu is <5 ppm.

[0102] (7) The secondary mixed material obtained in step (6) is transferred to a vacuum drying oven, dried at 100° C. and a vacuum degree of −0.7 MPa for 12 h, and then sieved using a 300-mesh nylon sieve to obtain a high-nickel ternary positive electrode material coated with a composite coating agent.

[0103] The twice-coated LiNi prepared in step (7) 0.88 Co 0.09 Mn 0.03 The button-type CR2025 half-cell made of O2 high-nickel ternary positive electrode material has a first discharge capacity of 221.9mAh / g ( Figure 5 ), the coulombic efficiency reached 91.2%; it was made into a cylindrical 18650 full battery for electrochemical performance testing. After 500 charge and discharge cycles at a cut-off voltage of 2.8-4.2V and a rate of 0.5C / 0.5C, the discharge specific capacity retention rate could reach more than 83.8%.

[0104] Comparative Example 1

[0105] Comparative example of embodiment 2:

[0106] Uncoated LiNi 0.83 Co 0.12 Mn 0.05 O2 cathode material ( Figure 2 ) The residual alkali content is 3820ppm, and it is made into a button CR2025 half-cell. At a cut-off voltage of 2.8-4.3V and a rate of 0.1C, the first discharge capacity reaches 207.7mAh / g ( Figure 6 ), the coulombic efficiency reached 88.5%; it was made into a 18650 cylindrical full battery for electrochemical performance testing. At a cut-off voltage of 2.8-4.2V, 0.5C / 0.5C charge and discharge cycles for 500 times, the capacity retention rate was 80.4%.

[0107] Comparative Example 2

[0108] Comparative example of embodiment 5:

[0109] Uncoated LiNi 0.80 Co 0.10 Mn 0.10 The residual alkali content of the O2 positive electrode material is 3460ppm. It is made into a button-type CR2025 half-cell. At a cut-off voltage of 2.8-4.3V and a rate of 0.1C, the first discharge capacity reaches 200.1mAh / g ( Figure 7 ), the coulombic efficiency reached 89.9%; it was made into a 18650 cylindrical full battery for electrochemical performance testing. At a cut-off voltage of 2.8-4.2V, 0.5C / 0.5C charge and discharge cycles for 500 times, the capacity retention rate was 81.1%.

[0110] Comparative Example 3

[0111] Comparative Example of Example 6:

[0112] Uncoated LiNi 0.88 Co 0.09 Mn 0.03 The residual alkali content of the O2 positive electrode material is 4340ppm. It is made into a button-type CR2025 half-cell. At a cut-off voltage of 2.8-4.3V and a rate of 0.1C, the first discharge specific capacity reaches 213.7mAh / g ( Figure 8 ), the coulombic efficiency reached 89.8%; it was made into a 18650 cylindrical full battery for electrochemical performance testing. At a cut-off voltage of 2.8-4.2V, 0.5C / 0.5C charge and discharge cycles of 400 times, the capacity retention rate was less than 80%.

[0113] Comparing the embodiments and comparative examples, the electrochemical properties of the high-nickel ternary positive electrode material prepared by the method of the present invention, such as the first discharge specific capacity and the capacity retention rate, are superior to those of the uncoated high-nickel positive electrode material.

[0114] The present invention starts from reducing the residual alkali content of the high-nickel ternary cathode material and improving the conductivity of the high-nickel ternary cathode material. The prepared high-nickel ternary cathode material includes an active material with the molecular formula LiNi x Co y Mn z O2 (0.8 ≤ x < 1, 0 < y < 0.2, 0 < z < 0.2, and x + y + z = 1), and a coating layer formed by a primary co - coating of aluminum phosphate and lithium phosphate and a secondary co - coating of a composite coating agent of graphene, carbon nanotubes, and conductive carbon black. It exhibits excellent discharge specific capacity performance and cycle stability, and will play potential and advantages in the situation where the requirements for energy density of power batteries are getting higher and higher.

[0115] The above is the preferred embodiment of the present invention. Any simple modification, equivalent change, and modification made to the above embodiment based on the technical essence of the present invention shall fall within the protection scope of the present invention.

Claims

1. A method for preparing a high-nickel ternary positive electrode material with low residual alkali, high specific capacity and high cycle stability, characterized in that: The following steps are involved: Step 1: Preparation of primary coating agent aluminum metaphosphate dispersion: Aluminum metaphosphate and nitrogen methyl pyrrolidone are mixed at a mass ratio of 0.01-0.03:1, and then added to a high-speed pre-disperser for pre-dispersion to form a premixed dispersion; then the premixed dispersion is transferred to a grinder, the grinder is turned on, and the dispersion is kept at a temperature of 5-15° C. and ground for 2-6 hours to obtain a ground dispersion; the ground dispersion is sand-milled and homogenized, and magnetic foreign matter is removed by a magnetic foreign matter removal device to form a primary coating agent aluminum metaphosphate dispersion with stable and uniform dispersion; Step 2: Mix the high nickel ternary positive electrode material with the primary coating agent aluminum metaphosphate dispersion: Mix the high-nickel ternary cathode material with the metaphosphoric acid aluminum dispersion as the primary coating agent in step 1 at a mass ratio of 0.5 to 1.5:1 and stir to mix evenly to obtain a primary mixed material; the molecular formula of the high-nickel ternary cathode material is LiNi x Co y Mn z O2, where 0.80 ≤ x < 1, 0 < y < 0.2, 0 < z < 0.2, and x + y + z = 1; Step 3: Vacuum drying of the mixed material: The primary mixed material in step 2 is vacuum dried and sieved to obtain a primary coated high-nickel ternary positive electrode material matrix; Step 4: Solid phase sintering of the high nickel ternary cathode material matrix: The high-nickel ternary positive electrode material substrate coated once in step 3 is placed in a box-type atmosphere resistance furnace, and sintered in an inert gas atmosphere with a flow rate of 30-60 L / h, and the temperature is increased to 580-620°C at a rate of 2-4°C / min and kept for 5-8 hours, and then cooled to 300°C at a rate of -0.3-0.5°C / min, and then naturally cooled to room temperature with the furnace, and the sintered material is sieved with a 200-400 mesh nylon sieve to obtain a high-nickel ternary positive electrode material powder co-coated with lithium phosphate, aluminum phosphate and aluminum metaphosphate; Step 5: Preparation of secondary coating agent dispersion: The composite coating agent, polyvinyl pyrrolidone and nitrogen methyl pyrrolidone are sequentially put into a high-speed pre-disperser for pre-dispersion to form a premixed dispersion; then the premixed dispersion is added to a grinder, the grinder is turned on, and the dispersion is kept at a temperature of 5-15°C for grinding for 4-8 hours to obtain a grinding dispersion; the grinding dispersion is sand-milled and homogenized to form a secondary coating agent dispersion with stable and uniform dispersion; the composite coating agent is composed of graphene, carbon nanotubes and conductive carbon black; in terms of mass percentage, the premixed dispersion contains 0.5-3% graphene, 0.5-3% carbon nanotubes, 0.5-1% conductive carbon black, 93-97% nitrogen methyl pyrrolidone, and 0.1-1% polyvinyl pyrrolidone; Step 6: Mixing the high nickel ternary positive electrode material powder co-coated with lithium phosphate, aluminum phosphate and aluminum metaphosphate with the secondary coating agent dispersion: The high nickel ternary positive electrode material powder co-coated with lithium phosphate, aluminum phosphate and aluminum metaphosphate in step 4 is uniformly mixed with the secondary coating agent dispersion in step 5 at a mass ratio of 0.5 to 1.5:1 to obtain a secondary mixed material; Step 7: Drying and screening of mixed materials: The secondary mixed material in step six is ​​dried and sieved to obtain a high-nickel ternary positive electrode material coated with a composite coating agent.

2. The method for preparing a high-nickel ternary positive electrode material with low residual alkali, high specific capacity and high cycle stability according to claim 1, characterized in that: In step 1, a high-speed pre-dispersion tank is used for pre-dispersion, the high-speed pre-dispersion stirring speed is 300~500r / min, and the stirring time is 30~60min.

3. The method for preparing a high-nickel ternary positive electrode material with low residual alkali, high specific capacity and high cycle stability according to claim 2, characterized in that: In step 1, the grinding machine speed is 2000-3000 r / min, the sand grinding homogenization time is 2-6 h, and the dispersion temperature is 5-15 °C.

4. The method for preparing a high-nickel ternary positive electrode material with low residual alkali, high specific capacity and high cycle stability according to claim 1, characterized in that: In step three, drying is performed in a blast drying oven at a drying temperature of 100-120° C. for a drying time of 10-20 h; and screening is performed using a 200-400 mesh nylon sieve.

5. The method for preparing a high-nickel ternary positive electrode material with low residual alkali, high specific capacity and high cycle stability according to claim 1, characterized in that: In step 4, the inert atmosphere is an argon atmosphere.

6. The method for preparing a high-nickel ternary positive electrode material with low residual alkali, high specific capacity and high cycle stability according to claim 1, characterized in that: In step six, the mixing equipment is a vacuum mixer, and the mixing time is 8 to 20 hours.

7. The method for preparing a high-nickel ternary positive electrode material with low residual alkali, high specific capacity and high cycle stability according to claim 1, characterized in that: In step seven, drying is performed in a vacuum drying oven with a vacuum degree of -0.2 to -0.7 MPa and drying at 80 to 110° C. for 10 to 20 hours; and screening is performed using a 200 to 400 mesh nylon sieve.

8. The method for preparing a high-nickel ternary positive electrode material with low residual alkali, high specific capacity and high cycle stability according to claim 1, characterized in that: The primary coating agent aluminum metaphosphate dispersion in step one and the secondary coating agent dispersion in step five are treated to remove magnetic foreign matter; the treatment to remove magnetic foreign matter is to use an 8000~10000Gs magnetic foreign matter removal device to remove magnetic foreign matter 4~8 times.

9. The method for preparing a high-nickel ternary positive electrode material with low residual alkali, high specific capacity and high cycle stability according to claim 8, characterized in that: The primary coating agent aluminum metaphosphate dispersion in step one and the secondary coating agent dispersion in step five have a main controlled impurity Fe element content of <50ppm, and a single element content of Cr, Ni, Zn or Cu of <10ppm.

10. A high nickel ternary positive electrode material with low residual alkali, high specific capacity and high cycle stability, characterized in that: The high-nickel ternary positive electrode material is prepared by the preparation method of a high-nickel ternary positive electrode material with low residual alkali, high specific capacity and high cycle stability as described in any one of claims 1 to 9, and the residual alkali content of the high-nickel ternary positive electrode material is less than 3000ppm.

Citation Information

Patent Citations

  • Device and method for removing magnetic foreign matter in lithium battery material

    CN105470579A

  • Al(PO3)3 coated NCM811 positive electrode material and preparation method thereof

    CN113224310A

  • Modification method of high-nickel ternary positive electrode material

    CN115148945A